Effects of precipitated size of water-soluble amide-containing polymers and pore size of filters on recovery of Pd nanoparticles dispersed in acetone solution including colloidal polymer. Issue 5 (19th September 2021) - Kasaishi, Wataru; Oyamada, Juzo; Morisada, Shintaro; Ohto, Keisuke; Kawakita, Hidetaka
ABSTRACT: When immobilized Pd nanoparticles (Pd NP) are used for the hydrogenation of nitrile butadiene rubber (NBR), some Pd NP leaks into the reaction medium. This Pd NP is expensive and must be recovered. In this study, Pd NP were recovered from an NBR acetone medium by precipitation with poly N -[2-(dimethylamino)ethyl] methacrylamide (poly(DAEMA)) and filtration. When poly(DAEMA) solution was added to the Pd NP NBR acetone solution, poly(DAEMA) interacted with Pd NP and formed a precipitate by dehydration. The poly(DAEMA) precipitate including trapped Pd NP was completely recovered by filtration through a filter with a pore size of 1 μm. Poly(acrylamide) solutions of different molecular weights were tested for Pd NP recovery, and those with high molecular weights formed large quantities of precipitates, resulting in low recovery percentages. The concentration and molecular weight of the polymer used for the recovery of Pd NP by nanoprecipitation and filtration must be chosen carefully for optimal recovery. Especially, 40 kDa of PAA and 1 μm filter pores were suitable for efficient Pd NP recovery.